The research of communication barriers of national and civic self-identification - Оstapenko, Iryna; Остапенко, Ірина (Київський національний університет імені Тараса Шевченка, 2017)
The article is devoted to the problem of of the impact of communicative barriers on the process of national and civic self-identification of youth.The author analyzed main approaches to study of the self-identification, the peculiarities of national and civic identity, as well as the role of communication barriers in national and civic self-identification of youth and also presented the results of empirical research and identified main types of communication barriers of national and civic self-identification of students. According to research results author defined that among com- munication barriers of national self-identification are dominate content-operational barriers, but individual psychological and social barriers are less there. Among communication barriers of civic self-identification are dominate individual psychological barriers, but content-operational barriers and social barriers are less there.

Стаття присвячена проблемі впливу комунікативних бар`єрів на процес національної та громадянської самоідентифікації молоді. Автором проаналізовано основні підходи до вивчення процесу самоідентифікації, розглянуто особливості визначення національної та громадянської ідентичності, визначено роль комунікативних бар`єрів у процесі національної та громадянської самоідентифікації молоді. Представлено результати емпіричного дослідження та визначено основні типи комунікативних бар'єрів національної та громадянської самоідентифікації студентської молоді. Згідно з результатами дослідження встановлено, що домінуючим типом комунікативних бар`єрів національної самоідентифікації є змістово- операціональні, а соціальні та індивідуально-психологічні представлені менше. Серед бар'єрів громадянської самоідентифікації переважають індивідуально-психологічні, а соціальні та змістово-операціональні бар'єри представлені менше.
Дослідження комунікативних бар'єрів національної та громадянської самоідентифікації молоді
Keywords: національна самоідентифікація; громадянська самоідентифікація; комунікативні бар'єри; ідентичність; national self-identification; civic self-identification; communication barriers; identity